Photoperiodic control of sugar release during the floral transition: What is the role of sugars in the florigenic signal? - Ortiz-Marchena, M Isabel (Plant Signal Behav, 2015)
Florigen is a mobile signal released by the leaves that reaching the shoot apical meristem (SAM), changes its developmental program from vegetative to reproductive. The protein FLOWERING LOCUS T (FT) constitutes an important element of the florigen, but other components such as sugars, have been also proposed to be part of this signal.(1-5) We have studied the accumulation and composition of starch during the floral transition in Arabidopsis thaliana in order to understand the role of carbon mobilization in this process. In A. thaliana and Antirrhinum majus the gene coding for the Granule-Bound Starch Synthase (GBSS) is regulated by the circadian clock(6,7) while in the green alga Chlamydomonas reinhardtii the homolog gene CrGBSS is controlled by photoperiod and circadian signals.(8,9) In a recent paper(10) we described the role of the central photoperiodic factor CONSTANS (CO) in the regulation of GBSS expression in Arabidopsis. This regulation is in the basis of the change in the balance between starch and free sugars observed during the floral transition. We propose that this regulation may contribute to the florigenic signal and to the increase in sugar transport required during the flowering process.